Hormone deprivation alters mitochondrial function and lipid profile in the hippocampus. Issue 1 (April 2017) - Zárate, Sandra; Astiz, Mariana; Magnani, Natalia; Imsen, Mercedes; Merino, Florencia; Álvarez, Silvia; Reinés, Analía; Seilicovich, Adriana
Abstract : Mitochondrial dysfunction is a common hallmark in aging. In the female, reproductive senescence is characterized by loss of ovarian hormones, many of whose neuroprotective effects converge upon mitochondria. The functional integrity of mitochondria is dependent on membrane fatty acid and phospholipid composition, which are also affected during aging. The effect of long-term ovarian hormone deprivation upon mitochondrial function and its putative association with changes in mitochondrial membrane lipid profile in the hippocampus, an area primarily affected during aging and highly responsive to ovarian hormones, is unknown. To this aim, Wistar adult female rats were ovariectomized or sham-operated. Twelve weeks later, different parameters of mitochondrial function (O2 uptake, ATP production, membrane potential and respiratory complex activities) as well as membrane phospholipid content and composition were evaluated in hippocampal mitochondria. Chronic ovariectomy reduced mitochondrial O2 uptake and ATP production rates and induced membrane depolarization during active respiration without altering the activity of respiratory complexes. Mitochondrial membrane lipid profile showed no changes in cholesterol levels but higher levels of unsaturated fatty acids and a higher peroxidizability index in mitochondria from ovariectomized rats. Interestingly, ovariectomy also reduced cardiolipin content and altered cardiolipin fatty acid profile leading to a lower peroxidizability index. In conclusion, chronic ovarian hormone deprivation induces mitochondrial dysfunction and changes in the mitochondrial membrane lipid profile comparable to an aging phenotype. Our study provides insights into ovarian hormone loss-induced early lipidomic changes with bioenergetic deficits in the hippocampus that may contribute to the increased risk of Alzheimer's disease and other age-associated disorders observed in postmenopause.